Cone opsin mislocalization in Rpe65-/- mice: A defect that can be corrected by 11-cis retinal - HUMPHRIES, PETER (The Association for Research in Vision and Ophthalmology, Inc., 2005)
PURPOSE: In retinal degenerative diseases, rod photoreceptors typically deteriorate more rapidly than cone photoreceptors. In the Rpe65(-/-) mouse, a model for Leber's congenital amaurosis, cones degenerate much more rapidly than rods. In this model, the retinoid processing pathway in the retinal pigment epithelium is disrupted, and 11-cis retinal is not generated. This study was designed to investigate the feasibility of restoring functional cones with exogenous 11-cis retinal. METHODS: Rpe65(-/-)::Rho(-/-) mice were used to remove any interference of rods and compared with wild-type (wt) mice. Pups were injected intraperitoneally with 11-cis retinal, starting at postnatal day (P)10, and were maintained in complete darkness. At P25, cone function was assessed with photopic single-flash and flicker ERGs. Cone survival was determined immunohistochemically with cone-specific antibodies, and cone opsin levels were obtained by quantitative RT-PCR. RESULTS: At P25, cone density and transcript levels of cone opsins were drastically reduced, but a minute cone electroretinogram was detected, indicating that the cones were functional. Confocal microscopy revealed that the cone opsins were mislocalized, suggesting that their transport to the outer segments was impaired. Intraperitoneal administrations of 11-cis retinal before P25 led to increased transport of cone opsins to the outer segments and preserved cones anatomically and functionally. CONCLUSIONS: The results suggest that the ligand is required during cone opsin synthesis for successful opsin trafficking and that without 11-cis retinal, cones may degenerate because of opsin mislocalization. These results may have important consequences for the treatment of cone dystrophies.
PUBLISHED
Keywords: Ophthalmology